PENGARUH ANGKA HARAPAN HIDUP TERHADAP PRODUK DOMESTIK REGIONAL BRUTO 34 PROVINSI DI INDONESIA - Sihaloho, Estro Dariatno; 1Alrivaldi Syahrizal Rusli , 1Alrivaldi Syahrizal Rusli (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This research aims to examine the impact of life expectancy on the growth rate of Gross Regional Domestic Product in 34 provinces in Indonesia. It uses data from 2014 to 2018 and employs a random effects model for panel data regression analysis. life expectancy is a measure of the average human life expectancy. The dependent variable is Gross Regional Domestic Product and the independent variable is Life Expectancy Rate (AHP). The study finds that life expectancy has a positive, statistically significant impact on per capita Gross Regional Domestic Product across the 34 provinces in Indonesia. This study also found that the average length of schooling, the human development index have positive and significant effect on regional economic growth in Indonesia. Meanwhile, population has a negative effect on regional economic growth in Indonesia. This suggests that investing in health in each province will lead to increased economic growth, as health investment contributes to the country's human capital.